مركز علاج طبيعي في الخليل - مضية, ريم (جامعة بوليتكنك فلسطين - معماري, 2020)
العلاج الطبيعي هو عبارة عن مهنة طبية يتم تقديمها للأفراد من أجل إعادة الحركة إلى الحد الأقصى والتطوير والحفاظ على القدرات الوظيفية في جميع المراحل العمرية التي يمر بها الشخص. يعمل العلاج الطبيعي في استعادة الحركة بعد تعرض المريض للإصابة أو المرض أو الإعاقة؛ ذلك بممارسة بعض التمارين الرياضية، والعلاج اليدوي، والتعليم، ويساعد في منع تفاقم بعض الأمراض، والتسريع في عملية الشفاء،ولذلك لأهمية العلاج الطبيعي وفوائده العديدة وعدم توفر مركز علاج طبيعي في المنطقة الجنوبية ، ولهذا يعتبر القيام بعمل مركز علاج طبيعي مهم لتلبية حاجات السكان . يهدف البحث لاعداد و الدراسة النظرية لتصميم مركز علاج طبيعيلتلبية احتياجات سكان المدينة بجميع فئاتها، بحيث يتم تجميع أكبر عدد من طرق العلاج الطبيعي ضمن مركزواحد، وجعلها الوجهة الصحيحة للعلاج الطبيعي من خلال استخدام أسلوب في التصميم المعماري يحقق الكفاءة في توفير أماكن مخصصة للعلاج الطبيعي . ولتحقيق ذلك اعتمدت الدراسة على المنهج التحليلي الوصفي، بحيث تم دراسة المعايير التخطيطية والتصميمة للمراكز العلاج الطبيعي،وكذلك دراسة الحالات الدراسية المشابهة وتحليلها، وتناول الكتب المختصة والدراسات العلمية بالاضافة للمواقع الالكترونية، وقد تم اعتماد الأرض بناء على اقتراح من بلدية مدينة الخليل، وعليه تم مراعاة الاستراتيجيات والشروط الخاصة بالعمل وعليه تمت الدراسة و الاطلاع على وجود المؤثرات الموقع. ويجب الاخذ بعين الاعتبار ان يضم المشروع كافة الاجنحة التي نحتاجها والتي توفر العلاج الطبيعي لأغلب الحوادث والامراض المنتشرة في الفترات الأخيرة . وقد أجريت الدراسة و التحليل على الموقع المعتمد و مدى تأثيره و تأثره بالبيئة، و قد أخذت طبوغرافية الموقع و المؤثرات البيئية بعين الاعتبار لغرض الوصول الى تصميم يتماشى مع طبيعة الموقع و يكون مراعيا للبيئة بغرص الاستفادة بقدر الامكان من امكانيات الطبيعة في التدفئة و التهوية . Physiotherapy is a medical profession that is offered to individuals in order to restore maximum mobility, development and maintain functional abilities at all stages of a person's life . After a patient has been injured, ill, or disabled. This is by practicing some exercises, manual therapy, and education, and it helps prevent the exacerbation of some diseases, and speeds up the healing process, and therefore the importance of physical therapy and its many benefits and the lack of a physical therapy center in the southern region, and this is why carrying out the work of a physical therapy center is important to meet the needs of the population. The research aims to prepare and theoretical study to design a physiotherapy center to meet the needs of the city’s residents in all its categories, so that the largest number of physiotherapy methods are collected within one center, and make it the correct destination for physical therapy through the use of an architectural design method that achieves efficiency in providing places designated for physical therapy. To achieve this, the study relied on the descriptive analytical method, so that the planning and design criteria of the physiotherapy centers were studied, as well as the study of similar case studies and their analysis, and specialized books and scientific studies in addition to the electronic sites were dealt with, and the land was approved based on a proposal from the Municipality of Hebron, and accordingly, it was taken into account. Strategies and conditions for work, and accordingly the study was conducted and the presence of site influences was examined. It must be taken into consideration that the project includes all the wards that we need and that provide natural treatment for most accidents and diseases prevalent in recent periods. The study and analysis were carried out on the approved site and the extent of its influence and impact on the environment, and the topography of the site and the environmental influences were taken into consideration in order to arrive at a design that is in line with the nature of the site and is environmentally friendly with the aim of making use of nature's capabilities in heating and ventilation as much as possible
CD, no of pages 49, معماري 9/2020
Keywords: التصاميم المعمارية; المراكز الصحية